The Multifaceted Contributions and Influence of Women during the French Revolution - Aminzai, Wafiullah; Dainsh, Mohibullah; Safi, Jamshed (International Journal of Contemporary Sciences (IJCS), 2025)
This paper examines the status and role of women during the French Revolution. The objective of this research is to analyze how women participated in various spheres, including political, social, and cultural activities, during this transformative period. Utilizing historical documents, literature, and feminist critiques, the findings highlight the increasing social and political influence of women while also addressing the limitations they faced. Ultimately, this paper concludes that despite their significant contributions, women’s rights were repressed after the revolution, necessitating greater recognition of their role in historical narratives.